Design Expert Optimization of Transdermal Patches for Effective Prolonged Release of Alzheimer's Medications - Rajasekhar, Bariki; Chinthaginjala, Haranath (Indian Journal of Pharmaceutical Education and Research)
Objectives: This study aimed to develop and characterize transdermal patches for Donepezil (DPZ) and Memantine (MMT) using a Box-Behnken Design (BBD), evaluating drug permeation at 8 hr, 16 hr, and 24 hr, with optimization through Design Expert software. Materials and Methods: The patches were formulated with HPMC K15, modified chitosan, and PVP K30. The physicochemical properties and drug infusion were tested and characterized. Results: The transdermal patches developed in this study were found to be soft and flexible, indicating good handling properties and potential for comfortable application. The patches demonstrated sustained drug release, extending beyond 24 hr, which is crucial for preserving consistent beneficial levels of DPZ and MMT in the systemic circulation. The optimal formulation, as identified through the BBD using Design Expert software, included HPMC K15 (125 mg), modified chitosan (65.91 mg), and PVP K30 (40 mg). This combination effectively facilitated prolonged drug penetration while keeping the flexibility and integrity of the patches. Conclusion: The study concludes that the formulated transdermal patches using HPMC K15, modified chitosan, and PVP K30 offer an effective means for prolonged delivery of DPZ and MMZ. The optimized patches support sustained discharge for a prolonged time, which can improve patient compliance and therapeutic outcomes in treating conditions like Alzheimer's disease. The use of a systematic design approach, such as the BBD, proved beneficial in optimizing the formulation parameters, ensuring the development of high-quality transdermal patches with desirable properties for clinical application.
Keywords: Box Behnken Design; Drug permeation; Extended release; Flexibility.